THE ACCOUNTING EXCHANGE. - Littleton, A. C. (The Accounting Review, 1947)
Abstract The verbs used in the literature of auditing tell what auditors do, and therefore take on technical significance. An analytical study of word usage, by detecting differing shades of word meaning, could therefore be expected to direct attention to differing types of audit action. In a sample of auditing literature amounting to approximately 1,720 pages, about 75 verbs were used 20 times or more for a total of over 5,000 uses. About 400 other verbs were used less than 20 times each for a total of 1,500 uses. The most notable feature of this quantitative analysis is the fact that within a large vocabulary of audit verbs there is a high concentration upon a few words. Seventeen verbs used 30 to 99 times are: note, accept, scrutinize, reconcile, disclose, count, give, substantiate, see, account for, report, request, state, confirm, analyze, satisfy, audit. Fifteen verbs used 30 to 49 times are: provide, insist, study, prove, foot, establish, discover, include, trace, adjust, show, detect, value, take, make.